2021
DOI: 10.1038/s41598-021-99532-1
|View full text |Cite
|
Sign up to set email alerts
|

Skeletally immature patient showed lower graft maturity than skeletally mature patient after ACL reconstruction with a rounded rectangular femoral tunnel

Abstract: To compare the clinical results and ligamentization of anterior cruciate ligament reconstruction (ACLR) between skeletally immature and mature patients. Two-hundred-and-two patients who underwent primary ACLR were evaluated retrospectively. The clinical outcomes were compared between skeletally immature (immature group 1, n = 27) and mature (control group 1, n = 175) groups. Graft ligamentization of the reconstructed anterior cruciate ligament (ACL) using magnetic resonance imaging (MRI) signal intensity at 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…[ 61 ] Am J Sports Med Retrospective 68 25.0 Trans-epiphyseal 19 19 13.4 10 Asai et al. [ 62 ] Sci Rep Retrospective 66 23.0 Trans-epiphyseal 27 27 13.9 16 Bonnard et al. [ 63 ] J Bone Joint Surg Br Retrospective 72 66.0 All-epiphyseal 56 56 12.2 13 Calvo et al.…”
Section: Resultsmentioning
confidence: 99%
“…[ 61 ] Am J Sports Med Retrospective 68 25.0 Trans-epiphyseal 19 19 13.4 10 Asai et al. [ 62 ] Sci Rep Retrospective 66 23.0 Trans-epiphyseal 27 27 13.9 16 Bonnard et al. [ 63 ] J Bone Joint Surg Br Retrospective 72 66.0 All-epiphyseal 56 56 12.2 13 Calvo et al.…”
Section: Resultsmentioning
confidence: 99%
“… 15 Wasserstein et al 28 analyzed more than 12,000 ACL reconstruction procedures and found that young age (15-19 years) was a significant independent risk factor for failure. Asai and colleagues 1 reported that 14.8% of skeletally immature patients required revision compared with 2.9% of adults. The explanation for this is likely multifactorial, including lower graft maturity rates, distinct intra-articular inflammatory environments, different autograft sizes and materials, and pediatric patients’ overall high activity levels and relative difficulty adhering to postoperative restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for this is likely multifactorial, including lower graft maturity rates, distinct intra-articular inflammatory environments, different autograft sizes and materials, and pediatric patients’ overall high activity levels and relative difficulty adhering to postoperative restrictions. 1 , 5 Finally, as pediatric patients have been shown to demonstrate significantly greater amounts of internal tibial rotation both before and after ACL reconstruction, 4 increased rotational instability has been a commonly cited reason for higher failure rates. Asai et al 1 reported that more than 20% of skeletally immature patients had persistent pivot shift postoperatively compared with a 4% positive postoperative pivot-shift rate in adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we observed that 10 miRNAs were detectable in both adult and adolescent groups with ACL tears without a meniscal tear. More pre-clinical studies are needed to better understand the intraarticular biochemical process in the healing potential of ACL tears in skeletally immature patients [ 41 , 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%